An analysis of reputational risks in Islamic banks in Malaysia with a proposed conceptual framework - Azrak, Tawfik; Saiti, Buerhan; Engku Ali, Engku Rabiah Adawiah (IIUM, 2016)
The most critical intangible asset that a bank possesses is its reputation. The reputation reflects a bank’s relative success in fulfilling the expectations of multiple stakeholders. Establishing a great reputation is a key element of organizational strategy, especially for banks. In case of Islamic banks, this is more important due to the nature of its business which is reputed to be defined by shariah principles. Any significant issues with regard to the operations of Islamic banks either in terms of shariah non-compliant financial products or customer complaints may damage the reputations of Islamic banks, thereby driving away customers, investors, shareholders and counterparties. As such, it is expected that Islamic banks pay more attention to managing reputational risks. This paper provides a review on the annual reports and financial statements of local and Islamic banks in Malaysia in order to assess the transparency of reporting and disclosing their reputational risk management framework. It is found that local domestic Islamic banks in Malaysia are more transparent compared to the locally incorporated foreign Islamic banks. Finally, we propose a framework for Islamic banks to manage reputational risks.